Implementasi Sistem Manajemen E -Comerce Dalam Penjualan Online Dengan Pendekatan Studi Kasus Pada Pt. Indja Mas Murni - Dela .; Moh Agung Surianto (CV. ITTC INDONESIA, 2026)
The development of digital technology and the rapid growth of marketplace platforms have encouraged companies to implement e-commerce management systems to increase online sales. PT. Indja Mas Murni, an aluminum kitchenware manufacturing company, adopted this system to expand market reach and improve operational efficiency. This study aims to analyze the implementation of an e-commerce management system in online sales, identify existing challenges, and examine strategies to improve sales performance.This study employed a qualitative descriptive approach using a case study method. The research population covered the online sales activities of PT. Indja Mas Murni, with key informants consisting of the company owner, operational manager, and marketing manager. Data were collected through interviews, observation, and documentation using primary and secondary data sources. Data analysis was conducted using descriptive qualitative analysis. The results indicate that PT. Indja Mas Murni has implemented an integrated e-commerce management system through marketplace utilization, cloud-based inventory management, integrated customer service, digital payment integration, and e-commerce analytics tools to monitor sales performance and analyze customer purchasing patterns. This implementation significantly increased online sales. However, challenges remain, including limited technological infrastructure, internal resistance to change, limited digital competencies, and system integration complexity. In conclusion, an e-commerce management system plays an important role in improving online sales and enhancing company competitiveness.